A Case of Severe Tricuspid Regurgitation Related to Traumatic Papillary Muscle Rupture - Ruchika Meel; Bongane Ngutshane; Ricardo Gonçalves; Shungu Mogaladi (Case Reports in Cardiology)
A 25-year-old male presented after a motor vehicle accident with tricuspid valve (TV) regurgitation, due to a flail TV secondary to papillary muscle rupture. We highlight the importance of three-dimensional echocardiographic imaging of the tricuspid valve and its utility in aiding a successful surgical repair.